Grazing behaviour, intake and performance of dairy ewes with restricted access time to berseem clover (Trifolium alexandrinum L.) pasture. (27th April 2016) - Molle, G.; Decandia, M.; Giovanetti, V.; Manca, C.; Acciaro, M.; Epifani, G.; Salis, L.; Cabiddu, A.; Sitzia, M.; Cannas, A.
Abstract: The effects of restricted access time to pasture (2, 4 or 6 h d −1 ; 2H, 4H or 6H) on ingestive behaviour and performance were assessed on four occasions per target grazing day (D1, initial day; D4, intermediate day; and D7, final day) in dairy ewes rotationally grazing berseem clover with a 7‐day grazing period and a 21‐day recovery period. A randomized block design with two replicates per treatment was used. All ewes were supplemented daily with 700 g per head of concentrates and 700 g per head of ryegrass‐based hay. Pasture subplot and animal group data were analysed by a factorial model including access time (AT), grazing day (D) and their interaction as fixed factors. Sward height decreased from D1 ( P  <   0·001) and green leaf mass from D4 ( P  <   0·001) onwards during the grazing period. Grazing time as a proportion of AT was higher in 2H than in 4H and 6H ewes on D1 and D4 but not on D7 ( P  <   0·05 for AT × D). Herbage intake rate was higher in 2H than in 4H and 6H ewes ( P  <   0·001). Herbage and total intakes were higher in 4H and 6H than in 2H ewes ( P  <   0·001), with herbage intake varying non‐linearly during the grazing period ( P  <   0·05). Milk yield was higher in 4H and 6H than in 2H ewes ( P  <   0·01). To conclude, despite the evidence of compensatory behaviour, restricting access time to 2 h d −1 constrained intake and performance of dairy ewes rotationally grazing berseem clover.